Structure of the assemblage of fruit-feeding butterflies in a high Andean anthropogenic landscape - Álvarez, Carlos Federico; Freitas, André Victor Lucci; Iserhard, Cristiano Agra; Giraldo, Carlos Eduardo; Uribe, Sandra Inés; Marín, Mario Alejandro (Journal of insect conservation, 2024)
The high Andean mountains are ecosystems subject to high human pressure activities, resulting in disturbed areas increasingly dominating the landscapes. However, there needs to have more knowledge about the contributions of different vegetation coverages and species to global diversity at the local level. For three consecutive years, we studied a guild of fruit-feeding butterflies in four different land covers (cloud forests, paramo, mixed anthropogenic habitats, and cattle pastures) in the northern Andes in Colombia, analyzing the diversity and structure of the butterfly assemblage in the region. The assembly showed significant differences between land covers. The mixed habitat was the most diverse in order q1 (exponential of Shannon entropy) and q2 (inverse of Gini-Simpson dominance index) diversity, and the cloud forest contained the higher abundance and species richness. Abundance decreased from forest to pasture, significantly reducing diversity in pastures, with cloud forest and paramo containing the key endemic species. These results indicate the value of landscape diversity in providing resources and conditions required for the diversity conservation of high Andean butterflies. Implications for insect conservation This study highlights the significance of the heterogeneity of natural landscape components in maintaining and preserving the diversity of butterfly assemblages in high Andean environments. Current conservation plans often tend to focus on paramo habitats, our findings highlight the crucial role of including the surrounding cloud forest and associated secondary forest in the design of effective conservation strategies. The analysis revealed a high complementarity between paramo and cloud forest assemblages, with each habitat type contributing significantly to the regional species pool. This underscores the interconnectedness and interdependence of these habitats, indicating that a comprehensive approach that considers both paramo and cloud forest ecosystems is essential for conserving the full diversity of butterfly species in the region. Moreover, our results demonstrate that cattle pastures exhibit extremely low butterfly species richness and possess a community structure that is distinctly different from native habitats.